pH-dependent dissociation from CTLA-4 in early endosomes improves both safety and antitumor activity of anti-CTLA-4 antibodies - Meiyu Zhang; Jinmei Li; Kepeng Yan; Haoyue Zhou; Song Mei; Benyu Wang; Dongyang Li; Xuexiang Du; Mingyue Liu; Peng Zhang; James K. Fields; Lei Ye; et al. (Proceedings of the National Academy of Sciences, 2025)
Anti-CTLA-4 Abs (ACAs) are a breakthrough for cancer therapy, but their potential is limited by immunotherapy-related adverse events (irAE). We previously reported that ACAs with acidic pH-sensitive binding to CTLA-4 exhibit higher antitumor activity with fewer irAE. We now test a panel of variants of Ipilimumab (Ipi), the first ACA cancer therapeutic, for tumoricidal efficacy and irAE. Surprisingly, not all pH-sensitive Ipi variants exhibited an enhanced therapeutic index. Ipi13, which retained binding to CTLA-4 at pH 6.0 but dissociated at lower pH, showed no enhancement. By contrast, Ipi25, which dissociates from CTLA-4 at pH 6.0, the pH of the early endosome (EE), showed greater tumor regression and less severe irAE. Confocal microscopy showed that Ipi13 maintained colocalization with CTLA-4 at the late endosomes (LE) and lysosomes resulting in lysosomal degradation of CTLA-4. Conversely, Ipi25 did not colocalize with CTLA-4 in LE or lysosomes after endocytosis but allowed both proteins to transfer to recycling endosomes. EE dissociation was also characteristic of variants of Tremelimumab (Treme), another clinical ACA, that showed better efficacy and fewer side effects. Thus, our data reveal the significance of early intracellular dissociation from CTLA-4 to improve ACAs for safer and more effective cancer immunotherapy.